Sirolimus as a promising drug therapy for blue rubber bleb nevus syndrome: Two-case report. (May 2022) - Ma, Jian-Xun; Xia, You-Chen; Zou, Li-Ping; Lin, Heng-Ju; Chang, Xu; Liu, Li-Ying; Toledo, Joy Roechelle A.
Blue rubber bleb nevus syndrome is a very rare systemic vascular malformation frequently affecting the skin and the gastrointestinal tract. The pathogenesis of the disease is still unclear, and the standard treatment does not exist. This study reports two blue rubber bleb nevus syndrome cases, of which the second patient received the TEK gene mutations detection and got a low-dose sirolimus therapy, compared with the first patient who was not treated with sirolimus. The report shows some positive findings of TEK gene mutations and the efficacy of sirolimus treatment. We postulate that the TEK gene mutations play an important role in the pathogenesis. The mutations of different locations of the TEK gene cause a wide range of activating TIE2 mutations, which could stimulate the mammalian target of rapamycin signaling pathways to mediate angiogenesis, resulting in different clinical phenotypes of cutaneomucosal venous malformations. Sirolimus could effectively block the upstream and downstream factors of mammalian target of rapamycin signaling pathways to achieve the antiangiogenic effect. The initial dose of sirolimus can be 0.05–0.1 mg/kg/d for a trough level of 5–15 μg/L in the treatment of blue rubber bleb nevus syndrome. However, a lower-dose sirolimus is also effective while minimizing the side effects.